(untitled) (Docentes 2.0 Journal, 2025)
There are rigid, authoritarian, and discriminatory classroom behaviors and attitudes, which must be modified by promoting inclusion processes, good treatment, and the practice of values. The study aimed to analyze the effect of democratic coexistence on the school climate. The research was based on the positive paradigm, hypothetical-deductive method, quantitative approach, non-experimental analytical design, and cross-sectional. The population was made up of 210 high school students, and the sample determined by the stratified probabilistic method was made up of 137 students. Regarding the technique, a survey and two questionnaires were developed as instruments, duly validated and of acceptable reliability. The results obtained through the ordinal logistic regression test show that the democratic coexistence model is plausible because the p-value < 0.05; Therefore, the model explains 73.7% of the school climate. It was also verified that the most influential dimension is autonomy and leadership, with 55.1%, and the least influential is the participation dimension, with 36.6%. Therefore, it is recognized that promoting a culture of respect for opinion and diversity among students and teachers contributes to creating an environment of harmony. Among the conclusions, it is highlighted that promoting a positive school climate through democratic coexistence forges a social and school environment consistent with students’ interests.